Developmental Relations Between ADHD Symptoms and Reactive Versus Proactive Aggression Across Childhood and Adolescence. Issue 12 (October 2020) - Murray, Aja Louise; Obsuth, Ingrid; Zirk-Sadowski, Jan; Ribeaud, Denis; Eisner, Manuel
Objective: Past research has provided some preliminary evidence that ADHD and reactive aggression have overlapping neurocognitive bases. Based on this, we tested the hypothesis that ADHD symptoms are closely coupled in developmental terms with reactive aggression, more so than with proactive aggression with which it has been postulated to be only indirectly linked.Method: We used latent growth curve analysis to estimate the developmental relations between ADHD symptoms and subtypes of aggressive behavior in a normative sample of 1, 571 youth (761 female, 810 male) measured from ages 7 to 15.Results: Individual ADHD trajectories were significantly and substantially correlated with individual trajectories in both aggressive subtypes; however, consistent with our hypothesis, the relation with reactive aggression was significantly stronger.Conclusion: Our study provides some of the first evidence for a differential relation between ADHD symptoms and aggression subtypes not only cross-sectionally but also in terms of their longitudinal developmental trajectories.